Founding a Company Handbook of Legal Forms in Europe - Munkert, Michael J.; Stubner, Stephan; Wulf, Torsten; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The book "Founding a Company - Handbook of Legal Forms in Europe" provides an easily accessible overview of the most important information any entrepreneur or manager needs when deciding for a legal form of the business. This makes it especially interesting for companies that decide to enter new markets within Europe and need to understand which requirements and advantages the different legal forms have. With the structured presentation of this information for ten different countries the book allows for quick comprehension and comparison of the aspects discussed. The book is a valuable resource for entrepreneurs, consultants and anybody who supports the business formation process in Europe as well as for lecturers and students working in this field.
The Need for a Better Understanding of Legal Forms in Europe -- Cross-Border Operations and Enlargement of European Union as Driving Forces for Pan-European Expansion Strategies -- Legislatory Need for a Handbook on Legal Forms in Europe and Selection of Countries -- Legal forms of company foundation -- Austria -- France -- Germany -- Hungary -- Italy -- The Netherlands -- Romania -- Spain -- Switzerland -- United Kingdom.
Keywords: Economics; Commercial law; Comparative law; Industrial management; Entrepreneurship; Economics/Management Science; Entrepreneurship; Commercial Law; Management/Business for Professionals; International & Foreign Law/Comparative Law